Protected area Economics and Policy: Linking Conservation and Sustainable Development - Munasinghe, Mohan; McNeely, Jeffrey A.; Schwab, Adelaida; International Union for Conservation of Nature and Natural Resources (Washington, D.C.: Distributed for the World Conservation Union by The World Bank, 1994)
The papers in this volume originated from the workshop on the Economics of Protected Areas at the IUCN-World Conservation Union Fourth World Congress on National Parks and Protected Areas, held in Caracas, Venezuela, during February 10-21, 1992. They seek to bring the techniques of environmental economics to bear on the vital task of improving the design and management of protected areas.
"The papers in this volume originated from the Workshop on the Economics of Protected Areas at the IUNC-World Conservation Union Fourth World Congress on National Parks and Protected Areas, held in Caracas, Venezuela, during February 10-21, 1992"--P. vii.
Includes bibliographical references.
ne 08/03/2018
Loan
Keywords: Sustainable Development; Conservation of Natural Resources; Natural Resources; Ecotourism